Settlement of Motorcycle Traffic Accidents by Children Causing Death - Pratama, Alfin Daniel; Prawesthi, Wahyu; Astutik, M. Sri (Rechtsvinding, 2025)
This study aims to analyse the forms of legal liability applicable to minors who operate motorcycles and cause fatalities in traffic accidents, as well as to examine the possibility of legal action against their parents. The phenomenon of underage individuals driving on public roads raises serious legal and social concerns, as it not only endangers traffic safety but also generates questions regarding the appropriate legal subject to be held responsible when accidents occur. This research employs an empirical legal research method, which relies on real-world data obtained through interviews, observations, and document analysis to examine how the law is applied in practice. The findings indicate that within the juvenile criminal justice system, legal accountability must prioritise the best interests of the child, respect for the child’s views, and the application of restorative justice through diversion mechanisms. Case resolution is directed toward reconciliation between the victim and the child offender, avoiding deprivation of liberty, and fostering a sense of responsibility in the child. Furthermore, the study identifies the potential for parental liability where parents are proven to have provided opportunities, means, or assistance that facilitated the commission of the criminal act, as stipulated in Articles 56 and 57 of the Indonesian Criminal Code. Accordingly, this study underscores the importance of fair law enforcement that remains oriented toward child protection, while also recognising parents as parties who may bear legal responsibility under certain conditions.